RELEVANCE OF INDIGENOUS KNOWLEDGE SYSTEM OF THE TRIBES OF ARUNACHAL PRADESH IN CORONA PANDEMIC – AN ANTHROPOLOGICAL APPROACH - Ghosh, Kundan (International Journal of Research -GRANTHAALAYAH, 2020)
Anthropology has always been interested in knowing different cultural aspects of different societies. Each culture has its ecological set up and historical background. The approach of cultural relativism has advocated the field workers to collect data out of field by preceding local people’s view point. Due to ongoing Covid-19 pandemic the whole country has been in lockdown since 24th of March, 2020 and when the author writes this article, it became 58 days lockdown and total confirmed case in India is 111601 (www.covid19india.org). Now we look at our study context i.e. Arunachal Pradesh. A 31-year man from Medo village in Lohit district of Arunachal Pradesh, was the first case of corona virus in state, who attended a congregation in Delhi’s Nizamuddin West. He is recovered on 16th April, 2020 and since then no other cases are notified in the state. So, automatically the question is raised what kind of strategies help the people of Arunachal Pradesh specially tribal people from spreading the virus in large scale.